1997
DOI: 10.1111/j.1748-7692.1997.tb00647.x
|View full text |Cite
|
Sign up to set email alerts
|

IN VITRO FERTILIZATION OF IN VITRO MATURED MINKE WHALE (BALAENOPTERA ACUTOROSTRATA) FOLLICULAR OOCYTES

Abstract: In vitro fertilization of follicular oocytes harvested from ovaries and matured in vitro was attempted for 55 minke whales (Balaenoptera acutorostrata) captured for Japanese research purposes in the Antarctic Ocean during the period from November 1995 to March 1996. In Experiment 1, effects of culture duration (96 h or 120 h) on maturation of follicular oocytes and addition of caffeine (5 mM) and/or heparin (100 pg/ml) on sperm penetration and pro‐nuclear formation were investigated. Spermatozoa recovered from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 23 publications
2
35
0
Order By: Relevance
“…In contrast to AI, handling is reduced and more embryos may be produced with the same semen dose. IVM or IVF have been tried in various species such as the mink whale (Balaenoptera acutorostrata) [20], African elephant (Loxodonta africana) [36], gorilla (Gorilla gorilla) [53], and zebra (Equus burchelli, Equus zebra) [47]. In our deer preservation program, we developed a method for repeated immature oocyte recovery on live sika deer hinds by laparoscopic OPU.…”
Section: In Vitro Production Of Embryosmentioning
confidence: 99%
“…In contrast to AI, handling is reduced and more embryos may be produced with the same semen dose. IVM or IVF have been tried in various species such as the mink whale (Balaenoptera acutorostrata) [20], African elephant (Loxodonta africana) [36], gorilla (Gorilla gorilla) [53], and zebra (Equus burchelli, Equus zebra) [47]. In our deer preservation program, we developed a method for repeated immature oocyte recovery on live sika deer hinds by laparoscopic OPU.…”
Section: In Vitro Production Of Embryosmentioning
confidence: 99%
“…Fukui et al [14,15] attempted in vitro fertilization (IVF) of in vitro matured minke whale follicular oocytes using frozen-thawed spermatozoa, but the number of cleaved oocytes following IVF was low (5-6% of inseminated oocytes). This low cleavage rate may be due to the high proportion of morphologically abnormal spermatozoa ascertained in the present study.…”
Section: Referencesmentioning
confidence: 99%
“…Addition of 10% wFF to IVM medium and adjustment of the osmolarity t o 3 9 0 m O s m p r o v i d e s a b e t t e r a n d m o r e physiological environment for in vitro maturation of common minke whale oocytes, although the osmolarity of wFF in common minke whales has not been examined [5]. Iwayama et al [4] reported that IVM medium containing 50% wFF resulted in a similar proportion (approximately 30%) of matured oocytes after IVM culture for 28-30 h compared with the previous studies using 96-120 h [1][2][3]. The present study compared two durations of IVM culture (30 or 40 h) using medium supplemented with 10% wFF for common minke whale oocytes and found that 40 h of IVM culture was superior to 30 h in terms of the proportion of in vitro matured oocytes.…”
Section: Discussionmentioning
confidence: 94%
“…Immediately after death, the vasa deferentia were carefully retrieved to prevent the possibility of contamination by seawater. The spermatozoa c o l l e c t e d f r o m t h e v a s a d e f e r e n t i a w e r e cryopreserved in liquid nitrogen as described previously [2,9]. Briefly, spermatozoa were diluted 5-fold with a cryopreservation medium (Tris-fructose based), and aliquots (0.5 ml) of the sperm suspension were put in micro-cryotubes.…”
Section: Collection and Cryopreservation Of Whale Spermatozoamentioning
confidence: 99%
See 1 more Smart Citation